A new FRET-based ratiometric fluorescent probe for the detection of SO2 derivatives in mitochondria of living cells. (October 2020) - Wang, Wei; Li, Na; Liu, Jin-Ting; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: We developed a new mitochondria-targeted ratiometric fluorescent probe (named PPA) for SO2 derivatives (HSO3 − /SO3 2− ) with a large (pseudo) Stokes shift (209 nm) based on FRET platform in which water-soluble ( E )-4-(4-(dimethylamino)styryl)-1-alkylpyridin-1-ium was chosen as acceptor moiety and phenothiazine oxide as donor moiety. Probe PPA showed specific response toward HSO3 − /SO3 2− over H2 S, GSH, Cys and Hcy. The recognition group underwent a nucleophilic addition reaction with HSO3 − /SO3 2− to give rise to clear dual-emission signal changes in enhanced blue channel and subdued red channel under a single wavelength excitation. Moreover, probe PPA was successfully used for the detection of endogenous HSO3 − /SO3 2− and bioimaging of mitochondria-targeted in living cells. Graphical abstract: Image 1 Highlights: A new ratiometric fluorescent probe (named PPA) for HSO3 − /SO3 2− based on FRET platform was developed. PPA showed a large pseudo Stokes shift (209 nm), high selectivity, sensitivity. PPA could target well mitochondria in cell image. PPA could image endogenous HSO3 − /SO3 2− in HepG2 cells.